Uncooked cornstarch for the prevention of hypoglycemic events. Issue 12 (22nd April 2022) - Della Pepa, Giuseppe; Vetrani, Claudia; Lupoli, Roberta; Massimino, Elena; Lembo, Erminia; Riccardi, Gabriele; Capaldo, Brunella
Abstract: Hypoglycemia is a pathological condition characterized by a low plasma glucose concentration associated with typical autonomic and/or neuroglycopenic symptoms, and resolution of these symptoms with carbohydrate consumption. Hypoglycemia is quite common in clinical practice, particularly in insulin-treated patients with diabetes and in other inherited or acquired conditions involving the regulation of glucose metabolism. Beyond symptoms that might strongly affect the quality of life, hypoglycemia can lead to short- and long-term detrimental consequences for health. Hypoglycemia can be prevented by appropriate changes in dietary habits or by relevant modifications of the drug treatment. Several dietary approaches based on the intake of various carbohydrate foods have been tested for hypoglycemia prevention; among them uncooked cornstarch (UCS) has demonstrated a great efficacy. In this narrative review, we have summarized the current evidence on the UCS usefulness in some conditions characterized by high hypoglycemic risk, focusing on some inherited diseases − i.e. glycogen storage diseases and other rare disorders − and acquired conditions such as type 1 diabetes, postprandial hypoglycemia consequent to esophageal-gastric or bariatric surgery, and insulin autoimmune syndrome. We also considered the possible role of UCS during endurance exercise performance. Lastly, we have discussed the dose requirement, the side effects, the limitations of UCS use, and the plausible mechanisms by which UCS could prevent hypoglycemia.